How do you find the integral of #(x^2)/(sqrt(4-(9(x^2))) #?

Answer 1

#int x^2/sqrt(4-9x^2)dx=-1/18xsqrt(4-9x^2)-2/27cos^(-1)((3x)/2)+c#

For this problem to make sense #4-9x^2>=0#, so #-2/3<=x<=2/3#. Therefore we can choose a #0<=u<=pi# such that #x=2/3cosu#. Using this, we can subsitute the variable x in the integral using #dx=-2/3sinudu#: #int x^2/sqrt(4-9x^2)dx=-4/27intcos^2u/(sqrt(1-cos^2u))sinudu=-4/27intcos^2udu# here we use that #1-cos^2u=sin^2u# and that for #0<=u<=pi# #sinu>=0#.
Now we use integration by parts to find #intcos^2udu=intcosudsinu=sinucosu-intsinudcosu=sinucosu+intsin^2u=sinucosu+intdu-intcos^2udu=sinucosu+u+c-intcos^2udu#. Therefore #intcos^2udu=1/2(sinucosu+u+c)#.
So we have found #int x^2/sqrt(4-9x^2)dx=-2/27(sinucosu+u+c)#, now we substitute #x# back for #u#, using #u=cos^(-1)((3x)/2)#, so #int x^2/sqrt(4-9x^2)dx=-1/9xsin(cos^(-1)((3x)/2))-2/27cos^(-1)((3x)/2)+c#.
We can further simplify this by using the definition of sines and cosines in terms of triangles. For a right triangle with an angle #u# at one of the non-right corners, #sinu="opposite side"/"longest side"#, while #cosu="adjacent side"/"longest side"#, since we know #cosu=(3x)/2#, we can pick the adjacent side to be #3x# and the longest side to be #2#. Using Pythagoras' theorem, we find the opposite side to be #sqrt(4-9x^2)#, so #sin(cos^(-1)((3x)/2))=sinu=1/2sqrt(4-9x^2)#. Therefore #int x^2/sqrt(4-9x^2)dx=-1/18xsqrt(4-9x^2)-2/27cos^(-1)((3x)/2)+c#.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the integral of ( \frac{x^2}{\sqrt{4-9x^2}} ), use the trigonometric substitution method. Let ( x = \frac{2}{3}\sin(\theta) ). Then, ( dx = \frac{2}{3}\cos(\theta) , d\theta ). Substitute these into the integral and simplify. You'll end up with ( \int \frac{4\sin^2(\theta)}{\sqrt{4 - 4\sin^2(\theta)}} , d\theta ). Use a trigonometric identity to simplify this to ( \int \frac{4\sin^2(\theta)}{\sqrt{4\cos^2(\theta)}} , d\theta ). Then, integrate using a trigonometric identity, and finally, substitute back ( x = \frac{2}{3}\sin(\theta) ) to obtain the result.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7